2024
DOI: 10.3390/toxics12030167
|View full text |Cite
|
Sign up to set email alerts
|

Acute Toxicity Assessment of Orally Administered Microplastic Particles in Adult Male Wistar Rats

Ivana Guševac Stojanović,
Dunja Drakulić,
Ana Todorović
et al.

Abstract: While the effects of chronic exposure to microplastic particles (MPs) are extensively studied, the outcomes of a single treatment have received relatively less attention. To investigate MPs’ potential acute toxicity, including their impact on general health status (victual consumption, sensorimotor deficits, and clinical toxicity signs) and serum biochemical parameters (markers of organ/tissue function and oxidative stress indicators), we administered thoroughly characterized MPs (1.4, 35, or 125 mg/kg), gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Studies have shown that due to their accumulation in cells and tissues, NPs/MPs can induce cytotoxicity [17], oxidative stress [18], genotoxicity [19], inflammation [20], and neurotoxicity [21], among others [22,23]. Hence, the aim of the present work was to describe the factors that increase the cytotoxicity of plastic NPs/MPs in vitro, with regard to cell viability, cell death, reactive oxygen species (ROS) induction, and genotoxicity.…”
Section: Introductionmentioning
confidence: 97%
“…Studies have shown that due to their accumulation in cells and tissues, NPs/MPs can induce cytotoxicity [17], oxidative stress [18], genotoxicity [19], inflammation [20], and neurotoxicity [21], among others [22,23]. Hence, the aim of the present work was to describe the factors that increase the cytotoxicity of plastic NPs/MPs in vitro, with regard to cell viability, cell death, reactive oxygen species (ROS) induction, and genotoxicity.…”
Section: Introductionmentioning
confidence: 97%